Focus: management information systems. Basic concepts of a database management system. - Fowler DG (Clinical Laboratory Science)
Laboratory information systems are now found in almost every clinical laboratory. Since laboratory information systems are simply database management systems, an understanding of how databases work can greatly enhance their usefulness. All data stored in a database must have property and relationship descriptions that axe stored in a data dictionary for use by the database management system. There are three different types of data relationships that can exist. These include one-to-one, one-to-many, and many-to-many. Types of databases include the flat file, relational, object-oriented, and main memory databases. Of these four types the relational database is the most commonly used in healthcare. This type of database offers many advantages to data storage and retrieval such as providing data independence, data sharing, data accuracy, ad hoc queries, report generation, database size, and importing. As new technology becomes available, the more recent database types such as object-oriented and main memory will become the database of choice for laboratory information systems.